2020
DOI: 10.1146/annurev-astro-032620-021859
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the Lyman-α Universe

Abstract: Hydrogen Lyman-α (Lyα) emission has been one of the major observational probes for the high-redshift Universe since the first discoveries of high- z Lyα-emitting galaxies in the late 1990s. Due to the strong Lyα emission originated by resonant scattering and recombination of the most abundant element, Lyα observations witness not only Hii regions of star formation and active galactic nuclei (AGNs) but also diffuse Hi gas in the circumgalactic medium (CGM) and the intergalactic medium (IGM). Here, we review Lyα… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
128
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(137 citation statements)
references
References 247 publications
(298 reference statements)
9
128
0
Order By: Relevance
“…Narrowband Lyα emitter wide field surveys, followed-up by spectroscopic multi-object observations, have produced a wealth of information on LAE clustering and the large-scale structure of galaxies at high z (e.g., Francis et al 2004;Matsuda et al 2005;Zheng et al 2016;Ouchi et al 2020). They cover a large volume: for example 200 × 200 × 80 Mpc 3 for the SILVER-RUSH survey (Ouchi et al 2018;Shibuya et al 2017), but at the expense of a bright limiting luminosity (typically ∼10 43 erg s −1 ) and sparse sampling (e.g., 179 LAEs for the Harikane et al 2019 study at z = 5.7 and 6.6, that is 5.6 × 10 −5 Mpc −3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Narrowband Lyα emitter wide field surveys, followed-up by spectroscopic multi-object observations, have produced a wealth of information on LAE clustering and the large-scale structure of galaxies at high z (e.g., Francis et al 2004;Matsuda et al 2005;Zheng et al 2016;Ouchi et al 2020). They cover a large volume: for example 200 × 200 × 80 Mpc 3 for the SILVER-RUSH survey (Ouchi et al 2018;Shibuya et al 2017), but at the expense of a bright limiting luminosity (typically ∼10 43 erg s −1 ) and sparse sampling (e.g., 179 LAEs for the Harikane et al 2019 study at z = 5.7 and 6.6, that is 5.6 × 10 −5 Mpc −3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stark et al 2010;Kusakabe et al 2020). At redshifts 𝑧 ∼ 6, the LAE fraction of bright 𝑀 UV −19 galaxies is about 40%, while it is about 10% at 𝑧 ≈ 3 (see Ouchi et al 2020 for a review). Thus, our findings about LAEs at 𝑧 ≈ 2 might apply to a significant fraction of the galaxy population at higher redshifts.…”
Section: Implications For Constraining Lyc 𝑓 Esc With Jwst: Can Strong Lines Do It All?mentioning
confidence: 99%
“…Perhaps most importantly, LyC constraints based on Ly𝛼 profiles can be extrapolated to higher redshifts with some confidence because LAEs at 𝑧 ≈ 2 − 6 are fundamentally similarin e.g., their sizes (e.g., Malhotra et al 2012;Paulino-Afonso et al 2018), UV slopes (e.g., , and Ly𝛼 line profiles corrected for IGM absorption (e.g., Hayes et al 2021). Further, Ly𝛼 LFs are almost unevolving across 𝑧 ≈ 2 − 6, therefore a luminositylimited survey at 𝑧 ≈ 2 would have a similar proportion of bright and faint LAEs as at higher redshifts (e.g., Sobral et al 2018;Herenz et al 2019;Ouchi et al 2020).…”
Section: Introductionmentioning
confidence: 96%
“…The only way we have of accurately recover the SFR of the galaxy using hydrogen emission lines is if we have the luminosity of one or more Balmer lines available. A useful review on the topic of Lyα modeling and observations that deserves mention is Ouchi et al (2020).…”
Section: Observations Of the Lyα Linementioning
confidence: 99%
“…Putting all these processes together we get an interesting, if a bit muddled, picture of what is happening in the universe at the first few billion years of cosmic time (Shapley et al 2003;Dijkstra 2017;Hernán-Caballero et al 2017;Karman et al 2017;Vanzella et al 2018;Marchi et al 2019). A recent review on the state of the Lyα observations can be found in Ouchi et al (2020). Modeling the Lyα line profile is useful to investigate the physical conditions of the galaxy interstellar medium.…”
Section: Introductionmentioning
confidence: 99%